Stereotype Perempuan dalam Film Yuni - Aldi Mohamad Ridwan; Leadya Raturahmi; Resty Mustika Pratiwi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Stereotypes of women in society often associate women with domestic roles, virginity, and the value of marriage as a measure of their success in life. This view strengthens patriarchal control which limits women's space in various aspects of life. This research aims to analyze the stereotypical depiction of women in the film "Yuni", which reflects patriarchal control, education and freedom of self-expression. This research uses a semiotic method based on Roland Barthes' theory, which focuses on the analysis of denotation, connotation and myth. This research uses a critical paradigm to understand the construction of reality about women as shown through symbols and signs in films. The unit of analysis is the selection and identification of scenes relevant to female stereotypes. The research results show that stereotypes that associate women with domestic roles result in strengthening patriarchal control and limiting women's potential to contribute optimally to society. In this research, the film "Yuni" succeeded in exploring various stereotypes faced by women in a socio-cultural context that is thick with traditional norms. One of the main issues that arises is how women are often positioned as sexual objects, where their appearance and physical attractiveness are the focus of attention, while their abilities and aspirations are often overlooked. This shows that even though women have great potential, they are often trapped in a narrow view that judges them based on physical aspects. It is hoped that this research will provide new insights into the representation of women in films and the importance of education and policies that support women's empowerment.